Substrate with conductive AlN epitaxial film and its manufacturing method
The substrate with a conductive AlN epitaxial film on a sapphire substrate achieves high surface flatness and conductivity by optimizing the AlN layer thickness, Si concentration, and heat treatment conditions, overcoming previous challenges of surface unevenness and conductivity.
Patent Information
- Application Number
- JP2020196391
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-26
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2040-11-26
AI Technical Summary
Existing methods struggle to achieve high surface flatness and conductivity for n-type AlN layers on sapphire substrates, with high Si doses causing surface unevenness and low doses failing to achieve conductivity.
A substrate with a conductive AlN epitaxial film is created by forming an AlN layer on a sapphire substrate with a specific thickness and Si concentration, followed by ion implantation and heat treatment in a nitrogen atmosphere to achieve a high oxygen concentration and low sheet resistance.
The method results in a substrate with an electroconductive AlN epitaxial film that has high surface flatness (RMS < 1 nm) and low sheet resistance (50 GΩ/□ or less), effectively addressing the challenges of surface unevenness and conductivity.
Smart Images

Figure 0007671444000002 
Figure 0007671444000003 
Figure 0007671444000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a substrate with a conductive AlN epitaxial film having an AlN layer on a sapphire substrate, and a method for producing the same. [Background technology]
[0002] Aluminum nitride (AlN) is a material with a large band gap and is known to be capable of n-type or p-type doping, which has led to its widespread use in high-voltage devices, deep-ultraviolet LEDs, optical waveguides, MEMS piezoelectric acoustic sensors, and other applications.
[0003] In Non-Patent Document 1, a dose of 5×10 Si was added to an AlN layer having a thickness of 1 μm on a sapphire substrate. 15 cm -2 It is described that conductive n-type AlN was obtained by ion implantation at 1000.degree. C. and then heating at 1400.degree. C. for 10 minutes. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Masakazu Kanechika, and Tetsu Kachi Appl. Phys. Lett. 88, 202106 (2006) Summary of the Invention [Problem to be solved by the invention]
[0005] Sapphire substrates are less expensive than SiC (silicon carbide) substrates. Therefore, the inventors conducted various studies to obtain a conductive n-type AlN layer on a sapphire substrate. In the process, they discovered that a high dose of Si (e.g., a dose of 5×10 15 cm -2It was found that when ion implantation is performed at a dose of 1000 ℃ or more, damage accumulated by ion implantation causes large surface irregularities of about 5 to 15 nm in RMS (root mean square height). 14 cm -2 ), no surface irregularities are generated even after heat treatment at 1600°C after ion implantation, and a flatness of about 0.5 nm RMS can be maintained; however, it was found that it was difficult to obtain a conductive n-type AlN layer.
[0006] In a substrate with a conductive AlN epitaxial film, in which a conductive n-type AlN layer is formed on a sapphire substrate, the surface of the AlN layer must have a certain degree of high surface flatness. That is, even if an AlN layer is formed on a sapphire substrate and then heat-treated at a high temperature after ion implantation, the surface flatness of the AlN layer must be high. The surface flatness is preferably, for example, RMS of 1 nm or less. In addition, the AlN layer in the substrate with a conductive AlN epitaxial film must have a sheet resistance of, for example, a predetermined resistance value or less as a conductivity. The sheet resistance of the AlN layer is preferably, for example, 50 GΩ / □ or less.
[0007] The present invention has been made in consideration of the above-mentioned circumstances, and its object is to provide a substrate with a conductive AlN epitaxial film having a highly flat surface and a conductive n-type AlN layer on a sapphire substrate, and a method for manufacturing the same. [Means for solving the problem]
[0008] As a result of extensive research by the inventors in order to achieve the above object, the inventors focused on oxygen concentration and completed the present invention described below.
[0009] In order to achieve the above object, the present invention provides a substrate with a conductive AlN epitaxial film, comprising: A sapphire substrate; an AlN layer formed on the sapphire substrate; The AlN layer is The thickness is 2 μm or more, The average Si concentration in the range of 0.2 μm to 0.5 μm deep from the surface on the side opposite to the sapphire substrate is 1×10 18 cm -3 More than 1×10 19 cm -3 is as follows: The average oxygen concentration in the range of 0.2 μm to 0.5 μm deep from the surface is 6×10 17 cm -3 The following is the result.
[0010] The conductive AlN epitaxial film-attached substrate according to the present invention further comprises: The surface may have a root mean square height of 1 nm or less.
[0011] In order to achieve the above object, the present invention provides a method for producing a substrate with a conductive AlN epitaxial film, comprising the steps of: an AlN layer formation step of forming an AlN layer on a sapphire substrate at a growth temperature of 1400° C. or less to a thickness of 2 μm or more; an ion implantation step of implanting Si ions into a surface of the AlN layer opposite to the surface facing the sapphire substrate; a heat treatment step of heat treating the AlN layer and the sapphire substrate at a temperature of 1300° C. or higher in a nitrogen atmosphere; The dose of the Si ions in the ion implantation step is 2×10 15 cm -2 is less than The heat treatment step is a step of increasing the average oxygen concentration in the range of 0.2 μm to 0.5 μm deep from the surface to 6×10 17 cm -3 The following applies.
[0012] The method for producing a substrate with a conductive AlN epitaxial film according to the present invention further comprises: The AlN layer forming step includes: a first AlN layer forming step of forming a first AlN layer as the AlN layer on the sapphire substrate at a growth temperature of 1400° C. or less; a preliminary heat treatment step of heat treating the first AlN layer and the sapphire substrate at a temperature higher than a growth temperature of the first AlN layer; The method may further include a second AlN layer forming step of forming a second AlN layer as the AlN layer on the first AlN layer at a growth temperature of 1400° C. or less.
[0013] The method for producing a substrate with a conductive AlN epitaxial film according to the present invention further comprises: The ion implantation step is performed so that the average Si concentration in the range of 0.2 μm to 0.5 μm deep from the surface is 1×10 18 cm -3 More than 1×10 19 cm -3 The following should be used.
[0014] The method for producing a substrate with a conductive AlN epitaxial film according to the present invention further comprises: The AlN layer forming step is performed by adjusting the average oxygen concentration in the range of 0.2 μm to 0.5 μm deep from the surface to 2×10 18 cm -3 The following should be used. Effect of the Invention
[0015] It is possible to provide a substrate with a conductive AlN epitaxial film, which has an n-type AlN layer having high surface flatness and a predetermined electrical conductivity on a sapphire substrate, and a method for manufacturing the same. In this substrate with a conductive AlN epitaxial film, the surface flatness of the AlN layer after implantation of Si ions and heat treatment can be set to 1 nm or less in RMS. In addition, in this substrate with a conductive AlN epitaxial film, the AlN layer can have a level of electrical conductivity such that its sheet resistance is 50 GΩ / □ or less. [Brief description of the drawings]
[0016] [Figure 1] 1 is a side cross-sectional view of a substrate with a conductive AlN epitaxial film according to the present invention. [Diagram 2] 1A to 1C are schematic cross-sectional views illustrating steps of a method for producing a conductive AlN epitaxial film-formed substrate according to the present invention. [Diagram 3] 4 is a graph showing the Si concentration and oxygen concentration in the depth direction in the AlN layer of Example 1. [Figure 4] 4 is a graph showing the carbon concentration and hydrogen concentration in the depth direction in the AlN layer of Example 1. [Diagram 5] 13 is a graph showing the Si concentration and oxygen concentration in the depth direction in the AlN layer of Example 2. [Figure 6] 11 is a graph showing the carbon concentration and hydrogen concentration in the depth direction in the AlN layer of Example 2. [Figure 7] 4 is a graph showing the Si concentration and oxygen concentration in the depth direction in the AlN layer of Comparative Example 1. [Figure 8] 4 is a graph showing the carbon concentration and hydrogen concentration in the depth direction in the AlN layer of Comparative Example 1. [Figure 9] 1 is a graph showing the Si concentration and oxygen concentration in the depth direction in the AlN layers of Comparative Examples 2 and 3. [Figure 10] 1 is a graph showing carbon concentration and hydrogen concentration in the depth direction in AlN layers of Comparative Examples 2 and 3. [Figure 11] 13 is a graph showing the Si concentration and oxygen concentration in the depth direction in the AlN layer after the second heat treatment in Comparative Example 4. [Figure 12] 13 is a graph showing the carbon concentration and hydrogen concentration in the depth direction in the AlN layer after the second heat treatment in Comparative Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] Prior to describing the embodiments of the present invention, the following points will be explained in advance.
[0018] In this specification, a layer that functions electrically as a p-type is referred to as a p-type layer, and a layer that functions electrically as an n-type is referred to as an n-type layer. On the other hand, a layer that does not function electrically as a p-type or n-type because specific impurities such as oxygen, hydrogen, carbon, and Si are not intentionally added is called an "undoped" layer. An undoped layer may contain unavoidable impurities during the manufacturing process, and specifically, a layer that has a small carrier density (e.g., 4×10 16 / cm 3 In this specification, when the impurity concentration is less than 100%, the material is referred to as “undoped.” The above values of the impurity concentration of Si, etc. are based on SIMS analysis.
[0019] The overall thickness of the AlN layer formed by epitaxial growth can be measured using an optical interference film thickness measuring device, and the impurity concentration of the AlN layer can be measured by SIMS analysis.
[0020] Hereinafter, a conductive AlN epitaxial film-attached substrate and a manufacturing method thereof according to an embodiment of the present invention will be described with reference to the drawings. Note that in each drawing, for the sake of convenience, the aspect ratio of the substrate and each layer is exaggerated from the actual ratio.
[0021] [Explanation of General Configuration] 1 shows a substrate 100 with a conductive AlN epitaxial film according to this embodiment. The substrate 100 with a conductive AlN epitaxial film includes a sapphire substrate 1 and an AlN layer 2 formed on the sapphire substrate 1. The AlN layer 2 has a thickness of 2 μm or more. The average Si concentration (hereinafter simply referred to as the average Si concentration) calculated as the arithmetic mean value in the range of 0.2 μm to 0.5 μm deep from the surface of the AlN layer 2 opposite to the side facing the sapphire substrate 1 (hereinafter simply referred to as the surface of the AlN layer 2) is 1×10 18 cm -3 More than 1×10 19 cm -3 The average oxygen concentration calculated as the arithmetic mean value in the range of 0.2 μm to 0.5 μm deep from the surface of the AlN layer 2 (hereinafter simply referred to as the average oxygen concentration) is 6×10 17 cm-3 More preferably, the average oxygen concentration is 5×10 17 cm -3 The following is the result.
[0022] [Explanation of each part] [Sapphire substrate] The sapphire substrate 1 is a carrier on which the AlN layer 2 is formed. The surface orientation of the sapphire substrate 1 on which the AlN crystal growth is performed may be the (0001) plane. The sapphire substrate 1 may have an off-angle in the range of 0.1° to 1°. The thickness of the sapphire substrate 1 may be, for example, 80 μm to 1400 μm.
[0023] [AlN layer] The AlN layer 2 is a layer formed of a III-V compound (AlN in this embodiment) that mainly contains Al as the group III and mainly contains nitrogen (N) as the group V.
[0024] As described below, the AlN layer 2 formed on the sapphire substrate 1 contains a predetermined amount of oxygen and is implanted with a predetermined amount of Si (silicon). The AlN layer 2 is an n-type semiconductor layer. Impurities (elements other than Al and N) other than the above-mentioned oxygen and Si impurities are not intentionally added to the AlN layer 2. However, the AlN layer 2 may contain unavoidable impurities such as hydrogen other than oxygen and Si during the manufacturing process, and other Group III elements such as Ga and In and other Group V elements may be present at impurity levels (for example, 1×10 21 cm -3 (below) may be included.
[0025] The average oxygen concentration and the average Si concentration of the AlN layer 2 in this embodiment are values measured by secondary ion mass spectrometry (SIMS). The average oxygen concentration and the average Si concentration are obtained by SIMS analysis, measuring in the depth direction from the surface of the AlN layer 2. Since the outermost surface of the AlN layer 2 may be affected by dirt, surface oxidation, etc., the average oxygen concentration and the average Si concentration are evaluated by calculating the average values near the surface of the AlN layer 2, that is, in the range of a depth of 0.2 μm to 0.5 μm from the surface of the AlN layer 2.
[0026] As described above, the average Si concentration in the range of 0.2 μm to 0.5 μm deep from the surface of the AlN layer 2 is 1×10 18 cm -3 More than 1×10 19 cm -3 The average oxygen concentration in this range is 6×10 17 cm -3 More preferably, it is 5×10 or less. 17 cm -3 The average Si concentration in this range is 1×10 18 cm -3 5×10 or more 18 cm -3 In this way, it is more preferable that the oxygen concentration in the vicinity of the surface of the AlN layer 2 is 6×10 or less. 17 cm -3 By incorporating Si at an appropriate concentration by setting the concentration at a low level below this while reducing the amount of ion implantation so as not to roughen the surface of the AlN layer 2 as described below, it is possible to obtain a flat AlN layer 2 that has conductivity with a sheet resistance of 50 GΩ / or less.
[0027] The thickness of the AlN layer 2 is 2 μm or more, and more preferably 2.5 μm or more. The thickness of the AlN layer 2 can be measured using a non-contact type film thickness meter, for example, an optical interference film thickness measuring device. In this embodiment, the thickness of the AlN layer 2 is measured using a value measured by an optical interference film thickness measuring device, NanoSpec 6100 (manufactured by Nano Metrics). The upper limit of the thickness of the AlN layer 2 is not particularly limited, but can be, for example, 10 μm.
[0028] The surface unevenness of the AlN layer 2 can be measured using a scanning probe microscope (SPM). In order to further form a semiconductor layer on the AlN layer 2, the surface unevenness of the AlN layer 2 is preferably at least 1 nm or less when evaluated by RMS (root mean square height). In this embodiment, the surface unevenness of the AlN layer 2 is measured using a scanning probe microscope, Dimension ICON (manufactured by Bruker AXS). The measurement conditions for the surface unevenness of the AlN layer 2 when evaluating the surface unevenness of the AlN layer 2 are a cantilever of Scan Analysis, Tapping mode (scan speed 1 Hz, Sample / line: 512), and a measurement range of 2 μm×2 μm square. The RMS is calculated based on the JIS standard (JIS B 0601:2013).
[0029] [Description of Manufacturing Method] A method for manufacturing the conductive AlN epitaxial film-formed substrate 100 will now be described.
[0030] As shown in FIG. 2, a manufacturing method for the substrate 100 with a conductive AlN epitaxial film includes an AlN layer formation process (steps A and B in FIG. 2) of forming an AlN layer 2 on a sapphire substrate 1, an ion implantation process (step C in FIG. 2) of implanting Si ions into the surface of the AlN layer 2 opposite to the side facing the sapphire substrate 1, and a heat treatment process (step D in FIG. 2) of heat treating the AlN layer 2 and the sapphire substrate 1 at a temperature of 1300° C. or higher in a nitrogen atmosphere.
[0031] In the AlN layer forming step, an AlN layer 2 is formed on the sapphire substrate 1 by epitaxial growth to a thickness of 2 μm or more to form a precursor of the substrate 100 with a conductive AlN epitaxial film. The AlN layer 2 is formed by forming a first AlN layer 21 and a second AlN layer 22. That is, the AlN layer forming step includes a first AlN layer forming step of forming the first AlN layer 21 as the AlN layer 2 on the sapphire substrate 1, a preliminary heat treatment step of heat treating the first AlN layer 21 and the sapphire substrate 1 (step A in FIG. 2), and a second AlN layer forming step of forming the second AlN layer 22 as the AlN layer 2 on the first AlN layer 21 (step B in FIG. 2). The first AlN layer forming step, the preliminary heat treatment step, and the second AlN layer forming step will be described later.
[0032] In the AlN layer forming step, the average oxygen concentration in the range of 0.2 μm to 0.5 μm deep from the surface of the AlN layer 2 (i.e., the surface of the second AlN layer 22) is set to 2×10 18 cm -3 Less than or equal to 1×10 18 cm -3 The AlN layer 2 is formed as follows. Hereinafter, the range from a depth of 0.2 μm to 0.5 μm from the surface of the AlN layer 2 will be simply referred to as the vicinity of the surface of the AlN layer 2. By keeping the oxygen concentration in the vicinity of the surface of the AlN layer 2 (i.e., the surface of the second AlN layer 22) low at the stage of the second AlN layer formation process, activation of Si by ion implantation in an ion implantation process described later can be promoted, and an increase in the oxygen concentration in the vicinity of the surface after the second heat treatment described later can also be suppressed.
[0033] In the AlN layer formation process, when forming the first AlN layer 21 and the second AlN layer 22, the oxygen concentration contained during epitaxial growth can be controlled within a specific range by controlling the growth temperature during epitaxial growth, as well as the growth pressure, growth rate, and V / III ratio (ratio of V group / III group).
[0034] In this embodiment, as an example of oxygen concentration control during the formation of the first AlN layer 21 and the second AlN layer 22, the growth temperature (the temperature of the sapphire substrate 1) is set to a low temperature of 1400° C. or less. The growth temperature of the AlN layer 2 is preferably 1200° C. or more and 1340° C. or less. This makes it easier to prevent oxygen from the sapphire substrate 1, the inner walls of the device, etc. from being mixed into the AlN layer 2 during epitaxial growth.
[0035] Furthermore, by setting the growth temperature to 1400°C or less, it becomes possible to control the oxygen concentration by the V / III ratio. For example, even at a temperature exceeding 1340°C, if the V / III ratio is set to 600 or more, the oxygen concentration in the vicinity of the surface of the AlN layer 2 can be controlled to be low. Furthermore, by setting the growth temperature to 1400°C or less, the oxygen concentration can also be controlled by other control factors such as the growth pressure and growth rate.
[0036] For example, the AlN layer 2 may be grown with a growth pressure of 5 torr to 150 torr, a growth rate of 0.3 μm / hour to 3 μm / hour, a V / III ratio of 100 to 3000, and an oxygen concentration within the above ranges.
[0037] In the first AlN layer forming step, as shown as step A in FIG. 2, the first AlN layer 21 is epitaxially grown on the sapphire substrate 1 by a CVD method (vapor phase growth method) such as an MOCVD method. The growth temperature of the first AlN layer 21 in the first AlN layer forming step is 1400° C. or less. The growth temperature of the first AlN layer 21 is preferably 1200° C. or more and 1340° C. or less. The first AlN layer 21 is preferably 1.5 μm or less in thickness to suppress the occurrence of cracks in the preliminary heat treatment step described later. It is more preferable that the first AlN layer 21 has a thickness of 0.3 μm or more and 1 μm or less. The epitaxial growth method is not limited to the CVD method, and other film formation methods such as a sputtering method and an MBE method can be used, but the MOCVD method is preferable from the viewpoint of improving crystal quality.
[0038] The preliminary heat treatment step is performed after the first AlN layer formation step. In the preliminary heat treatment step, the first AlN layer 21 and the sapphire substrate 1 are heat treated (first heat treatment) at a temperature higher than the growth temperature of the first AlN layer 21. The temperature of the first heat treatment is preferably 1500°C or higher. Moreover, the temperature of the first heat treatment is preferably 1800°C or lower.
[0039] Immediately after the first AlN layer 21 is formed on the sapphire substrate 1, the first AlN layer 21 may contain many dislocations due to lattice mismatch with the sapphire substrate 1. However, by subjecting the first AlN layer 21 to a heat treatment at 1500° C. or higher after it is formed on the sapphire substrate 1, the dislocation density can be reduced. This can improve the crystallinity of the first AlN layer 21.
[0040] In the preliminary heat treatment step, oxygen is diffused from the sapphire substrate 1 into the first AlN layer 21. This oxygen is necessary for improving the crystallinity of the first AlN layer 21. The oxygen diffused from the sapphire substrate 1 diffuses widely into the first AlN layer 21. After the heat treatment, the first AlN layer 21 contains a large amount of oxygen.
[0041] The average oxygen concentration in the first AlN layer 21 after the preliminary heat treatment step in the range where the influence of oxygen diffusion is large from the interface with the sapphire substrate 1 to the surface of the first AlN layer 21 (the range from the interface with the sapphire substrate 1 to 0.5 μm) is 1×10 19 cm -3 It is preferable that the concentration is 1×10 or more. 20 cm -3 More preferably, it is equal to or greater than this.
[0042] In the second AlN layer formation process (step B in FIG. 2), the second AlN layer 22 is epitaxially grown on the first AlN layer 21 (on the surface of the first AlN layer 21 opposite the side facing the sapphire substrate 1) by a CVD method such as an MOCVD method.
[0043] The second AlN layer 22 is formed thicker than the first AlN layer 21. The second AlN layer 22 is preferably formed to a thickness such that the total thickness of the second AlN layer 22 and the first AlN layer 21 is 2 μm or more. For example, the second AlN layer 22 is preferably formed to a thickness of 1 μm or more and 9 μm or less, more preferably 1.7 μm or more, and even more preferably 2 μm or more. The growth temperature of the second AlN layer 22 in the second AlN layer forming step is 1400° C. or less. The growth temperature of the second AlN layer 22 is preferably 1200° C. or more and 1340° C. or less. The second AlN layer 22 is formed to have a lower oxygen concentration than the first AlN layer 21. In the second AlN layer forming step, as in the first AlN layer forming step, the epitaxial growth method is not limited to the CVD method, and other film formation methods such as the sputtering method and the MBE method can be used, but the MOCVD method is preferable from the viewpoint of improving the crystal quality.
[0044] Immediately after the AlN layer formation step, the AlN layer 2 is undoped except for the above-mentioned diffusing oxygen. The thickness of the AlN layer 2 is the sum of the thickness of the first AlN layer 21 and the thickness of the second AlN layer 22.
[0045] The ion implantation step (step C in FIG. 2) is performed after the second AlN layer formation step. In the ion implantation step, Si ions are implanted from the surface of the AlN layer 2. In the ion implantation step, the average Si concentration in the vicinity of the surface of the AlN layer 2 is set to 1×10 18 cm -3 More than 1×10 19 cm -3 The average Si concentration in the vicinity of the surface of the AlN layer 2 is preferably 5×10 18 cm -3 By setting the average Si concentration in the vicinity of the surface of the AlN layer 2 to be within the above-described range, the sheet resistance of the conductive AlN epitaxial film-formed substrate 100 can be reduced to an appropriate value to ensure conductivity, while reducing the surface irregularities of the AlN layer 2 after a heat treatment, which will be described later.
[0046] The implantation direction (irradiation direction) of the Si ions is tilted from the direction perpendicular to the (0001) plane of the sapphire substrate 1. However, if the Si ions are implanted completely perpendicular to the (0001) plane of the sapphire substrate 1, the Si ions may be implanted beyond a depth of 0.5 μm from the surface of the AlN layer 2 (for example, to a depth of 1 μm) due to a channel effect, and the concentration of Si may not be appropriately controlled. Therefore, it is preferable to tilt the implantation direction, and in this case, the tilt angle during Si ion implantation is preferably 0.1° to 10°, for example, and more preferably 7°.
[0047] In the ion implantation process, the voltage during Si ion implantation may be changed stepwise from high to low in several steps, for example, 90 keV for the first step, 40 keV for the second step, and 10 keV for the third step, and Si ions may be implanted while the voltage is changed stepwise from high to low. This makes it possible to make the Si concentration in the depth direction from the surface of the AlN layer 2 (for example, the Si concentration in the range from the surface of the AlN layer 2 to a depth of 0.1 μm) uniform. For example, the acceleration voltage may be selected according to the thickness of the AlN layer 2, and is preferably at least 1 keV, and more preferably selected in the range of 10 keV to 200 keV.
[0048] In the ion implantation process, the Si dose (total Si dose when Si ions are implanted in multiple steps) is set to 2 × 10 15 cm -2 The dose of Si is more preferably less than 2×10 14 cm -2 More than 1×10 15 cm -2 By setting the Si dose amount to the AlN layer 2 within the concentration range described above, the sheet resistance of the conductive AlN epitaxial film-formed substrate 100 can be reduced to an appropriate value to ensure conductivity, while reducing the surface irregularities of the AlN layer 2 after a heat treatment described below.
[0049] The heat treatment process (step D in FIG. 2) is carried out after the ion implantation process. In the heat treatment process, a precursor of the conductive AlN epitaxial film-formed substrate 100 is exposed to a temperature environment of 1300° C. to 1700° C. for a predetermined heat treatment time (hereinafter, this may be referred to as a second heat treatment). The heat treatment time of the second heat treatment is preferably 10 minutes to 60 minutes. As a heat treatment furnace used for the second heat treatment, for example, an ultra-high temperature furnace SR1800TS (manufactured by Thermo Riko Co., Ltd.) can be used.
[0050] During this second heat treatment, oxygen diffuses from the sapphire substrate 1 to the AlN layer 2. More specifically, the diffusion of oxygen from the sapphire substrate 1 proceeds from the interface between the sapphire substrate 1 and the AlN layer 2 toward the surface of the AlN layer 2. Note that during the second heat treatment, oxygen is also released from the outermost surface of the AlN layer 2.
[0051] The diffusion of oxygen from the sapphire substrate 1 during the second heat treatment generally remains within a range of up to 2 μm from the interface between the sapphire substrate 1 and the AlN layer 2. Since the first AlN layer 21 in which sufficient oxygen has already been diffused by the first heat treatment exists, further diffusion of oxygen from the sapphire substrate 1 to the portion that was the first AlN layer 21 becomes slow during the second heat treatment. The diffusion of oxygen into the second AlN layer 22 is mainly the diffusion of oxygen at the interface between the first AlN layer 21 and the second AlN layer 22. Therefore, the diffusion of oxygen from the interface toward the inside of the second AlN layer 22 is mainly only the elimination of the difference in oxygen concentration at the interface between the first AlN layer 21 and the second AlN layer 22 before the second heat treatment. This is because the diffusion of oxygen from the sapphire substrate 1 to the second AlN layer 22 (through the first AlN layer 21) is suppressed. Therefore, the oxygen concentration in the vicinity of the sapphire substrate 1 is high (the average oxygen concentration from the interface with the sapphire substrate 1 to 0.5 μm is 1×10 19 cm -3Even if the thickness of the AlN layer 2 is 2 μm or more, an increase in the oxygen concentration on the surface side of the AlN layer 2 can be suppressed even if the second heat treatment is performed within a necessary range in this embodiment, so long as the thickness of the AlN layer 2 is 2 μm or more. Also, by forming the second AlN layer 22 thicker than the first AlN layer 21 in the second AlN layer formation step, it is preferable to obtain the effect of suppressing an increase in the oxygen concentration near the surface of the AlN layer 2.
[0052] The second heat treatment is performed so that the average oxygen concentration in the vicinity of the surface of the AlN layer 2 is 5×10 17 cm -3 and the average Si concentration in the vicinity of the surface of the AlN layer 2 is 1×10 18 cm -3 More than 1×10 19 cm -3 The average Si concentration in the vicinity of the surface of the AlN layer 2 is 5×10 18 cm -3 After the second heat treatment, the average oxygen concentration of the AlN layer 2 from the interface with the sapphire substrate 1 to 0.5 μm is preferably 1×10 19 cm -3 More preferably, it is equal to or greater than this.
[0053] The second heat treatment is preferably performed in a state where the intrusion of oxygen from the outside is suppressed. In this embodiment, as the heat treatment in a state where the intrusion of oxygen is suppressed, the heat treatment is performed in a nitrogen atmosphere so as not to cause decomposition of the AlN layer 2. The nitrogen atmosphere is obtained, for example, by evacuating the inside of the heat treatment furnace and then passing nitrogen gas through the heat treatment furnace. The nitrogen pressure of the nitrogen atmosphere is normal pressure (10 5 Pa) even at reduced pressure (10 2 Pa or more 10 4 A reduced pressure is preferable because it is easier to reduce the oxygen concentration in the vicinity of the surface of the AlN layer 2.
[0054] In the second heat treatment, regardless of whether the nitrogen atmosphere is normal pressure or reduced pressure, it is preferable to evacuate the heat treatment furnace before heating to remove as much oxygen as possible from the furnace. A rotary pump (RP) may be used to evacuate the heat treatment furnace, but a turbomolecular pump (TMP) is preferably used. When evacuating with a rotary pump, there is a possibility that the oxygen concentration in the AlN layer 2 after the heat treatment is unintentionally high due to oxygen remaining in the furnace. However, when evacuating with a turbomolecular pump, it is possible to evacuate to a higher degree of vacuum than when using a rotary pump, and therefore such a problem can be avoided.
[0055] In this embodiment, by heat-treating the precursor of the conductive AlN epitaxial film-coated substrate 100 while suppressing the inclusion of oxygen as described above, when the AlN layer 2 is 2 μm or more thick, it is possible to suppress an increase in the average oxygen concentration near the surface of the AlN layer 2 after heat treatment.
[0056] As described above, in the present embodiment, in the AlN layer forming step, the thickness of the AlN layer 2 is set to 2 μm or more, and the average oxygen concentration in the vicinity of the surface of the AlN layer 2 is set to at least 2×10 18 cm -3 The AlN layer 2 is formed by reducing the average oxygen concentration in the vicinity of the surface of the AlN layer 2 after the heat treatment in the heat treatment step to 6×10 17 cm -3 It can be as follows:
[0057] In addition, when the thickness of the AlN layer 2 is thin, specifically, when the thickness is less than 2 μm, oxygen diffused from the sapphire substrate 1 by the heat treatment diffuses to the surface of the AlN layer 2, and the oxygen concentration on the surface side of the AlN layer 2 increases, and the average oxygen concentration in the vicinity of the surface of the AlN layer 2 becomes 6×10 17 cm -3 There are cases where it is not possible to do the following:
[0058] Furthermore, if the heat treatment time in the heat treatment step is much longer than 60 minutes (for example, if the heat treatment is continued for 24 hours), the amount of Si near the surface that is ion-implanted by the second heat treatment that diffuses toward the sapphire substrate becomes too large, which may reduce the effect of the present invention. It is believed that the adjustment of the distortion near the surface caused by the damage accumulated by the ion implantation (change in surface roughness) is completed within 60 minutes. EXAMPLES
[0059] An example of the conductive AlN epitaxial film-attached substrate according to this embodiment will be described.
[0060] Example 1 First, an AlN layer was epitaxially grown on a sapphire substrate (diameter 2 inches, film thickness: 430 μm, surface orientation: (0001), m-axis off-angle θ: 0.11 degrees) using the MOCVD method to form a precursor of a substrate with a conductive AlN epitaxial film. Hereinafter, this precursor (including one that has been processed as described below) may be simply referred to as a sample.
[0061] (AlN layer formation process) The formation of an AlN layer on a sapphire substrate by MOCVD was carried out as follows.
[0062] (First AlN layer formation process) First, a sapphire substrate was placed on the stage in the MOCVD apparatus, the stage temperature (corresponding to the growth temperature) was set to 1330°C, TMA gas (43sccm) and ammonia gas (250sccm) were flowed, and the first AlN layer was formed to a thickness of 0.5μm. The V / III ratio was 346.
[0063] (Preliminary heat treatment process) Next, the sample was transferred to a heat treatment furnace and subjected to a first heat treatment at 1600° C. in a nitrogen atmosphere for 5 hours.
[0064] (Second AlN layer formation process) Furthermore, the sample was placed on the stage in the MOCVD apparatus, the stage temperature (corresponding to the growth temperature) was set to 1330°C, and TMA gas (43 sccm) and ammonia gas (500 sccm) were flowed to form the second AlN layer with a thickness (film thickness) of 2.0 μm. The V / III ratio was 692. As a result, the total thickness of the AlN layer including the first AlN layer and the second AlN layer was 2.5 μm. The thickness of the AlN layer was measured using NanoSpec 6100 (manufactured by Nano metrics) at a total of 25 equally spaced locations, including the center of the surface on the AlN layer side of the sample. The following film thickness measurements were performed in the same manner.
[0065] The RMS of the surface of the AlN layer of the sample after the formation of the second AlN layer was 0.34 nm. The RMS was measured using the Dimension ICON (manufactured by Bruker AXS) mentioned above. The same was used for the following RMS measurements. In addition, the half-width of the rocking curve of AlN was evaluated using an X-ray diffractometer D8 (manufactured by Burker), and was found to be 113 seconds for the (0002) plane and 330 seconds for the (10-12) plane.
[0066] (Ion implantation process) Next, Si ions were implanted into the surface of the AlN layer of the sample after the formation of the second AlN layer. The implantation (acceleration) energy was changed in three steps, in the order of 90 keV, 40 keV, and 10 keV, so that the Si ions were uniformly implanted from the surface of the AlN layer to a depth of 0.1 μm. The implantation direction of the Si ions was tilted by 7 degrees from the (0001) plane. The total dose of Si ions was 5.0×10 14 cm -2 The RMS of the AlN layer surface after Si ion implantation was 0.5 nm.
[0067] Next, the Si concentration, oxygen concentration, carbon concentration and hydrogen concentration of the AlN layer of the sample after the Si ion implantation were measured by SIMS. Note that in FIG. 3, the Si concentration and oxygen concentration in the depth direction of the AlN layer after the Si ion implantation in Example 1 are shown by dashed lines. The graph on the right side of FIG. 3 shows the Si concentration. The graph on the left side of FIG. 3 shows the oxygen concentration. In FIG. 3, the vertical axis of each graph is concentration (cm -3 ), and the horizontal axis represents the depth (μm) from the surface of the AlN layer. Also in Fig. 4, the carbon concentration and hydrogen concentration in the depth direction of the AlN layer after Si ion implantation in Example 1 are shown by dashed lines. The graph on the right side of Fig. 4 shows the carbon concentration. The graph on the left side of Fig. 4 shows the hydrogen concentration. In Fig. 4, the vertical axis of each graph is the concentration (cm -3 ), and the horizontal axis is depth (μm).
[0068] The average Si concentration in the region from the surface of the AlN layer to a depth of 0.1 μm is 3 × 10 19 cm -3 The average Si concentration in the range of 0.2 μm to 0.5 μm deep from the surface of this AlN layer was 1×10 18 cm -3 The average oxygen concentration in the range of 0.2 μm to 0.5 μm deep from the surface of the AlN layer was 1×10 17 cm -3 In the following description, the Si concentration and oxygen concentration of the AlN layer are values obtained by SIMS unless otherwise specified. In addition, in the following description, the range from the surface of the AlN layer to a depth of 0.2 μm to 0.5 μm is simply referred to as the vicinity of the surface of the AlN layer.
[0069] (Heat treatment process) Next, the sample after the Si ion implantation was heat-treated (second heat treatment) using Thermo Riko SR1800TS to produce a substrate with a conductive AlN epitaxial film of Example 1. This heat treatment was performed as follows. That is, the sample was first placed in a furnace, and then evacuated with a RP, and then further evacuated with a TMP. The vacuum was set to a degree of vacuum of 5×10 -4The substrate was heated at 1600°C for 30 minutes under a nitrogen atmosphere at a reduced pressure of 100 Pa while being evacuated with a RP. The substrate was then cooled in a furnace while being subjected to nitrogen gas flow. After cooling, the RMS of the surface of the AlN layer of the substrate with the conductive AlN epitaxial film was 0.4 nm.
[0070] In the AlN layer before the second heat treatment, high concentration of Si ions were implanted from the surface of the AlN layer to a depth of 0.1 μm, but in the AlN layer after the second heat treatment (substrate with conductive AlN epitaxial film after cooling), the implanted Si had diffused to a depth of about 1 μm. In the AlN layer after the second heat treatment, the average Si concentration in the range from the surface of the AlN layer to a depth of 0.2 μm to 0.5 μm was 3×10 18 cm -3 3 further shows, by solid lines, graphs of the Si concentration and the oxygen concentration in the depth direction of the AlN layer after the second heat treatment in Example 1. Also, in FIG. 4 further shows, by solid lines, graphs of the carbon concentration and the hydrogen concentration in the depth direction of the AlN layer after the second heat treatment in Example 1.
[0071] In the AlN layer after the second heat treatment, the oxygen concentration was decreased compared to before the second heat treatment. In the AlN layer after the second heat treatment, the average oxygen concentration in the vicinity of the surface of the AlN layer was 4×10 16 cm -3 It was.
[0072] Furthermore, rectangular electrodes (50 μm × 100 μm) were formed in multiple locations on the surface of the AlN layer of the conductive AlN epitaxial film-coated substrate. These rectangular electrodes were formed by laminating a Ti layer (20 nm thick), an Al layer (100 nm thick), a Ni layer (20 nm thick), and a Au layer (50 nm thick) in that order. These rectangular electrodes were arranged with different interelectrode distances.
[0073] Using a four-point manual prober and a semiconductor characteristic evaluation system (Agilent B1599T), a voltage of up to 30 V was applied between these rectangular electrodes, and TLM measurements were performed on the conductive AlN epitaxial film-coated substrate. The TLM measurements showed that a current flowed and the sheet resistance was 23 GΩ / □.
[0074] Example 2 A substrate with a conductive AlN epitaxial film of Example 2 was prepared in the same manner as Example 1, except that the AlN layer was formed under the conditions of flowing TMA gas (43 sccm) and ammonia gas (250 sccm) and setting the V / III ratio to 346.
[0075] The RMS of the surface of the AlN layer of the sample after the second AlN layer was formed was 0.42 nm.
[0076] The RMS of the surface of the AlN layer of the sample after Si ion implantation was 0.5 nm. The average Si concentration in the range from the surface of this AlN layer to a depth of 0.1 μm was 3 × 10 19 cm -3 The average Si concentration near the surface of this AlN layer was 4 × 10 18 cm -3 The average oxygen concentration near the surface of this AlN layer was 8 × 10 17 cm -3 It was.
[0077] The RMS of the surface of the AlN layer of the sample after the second heat treatment was 0.5 nm. In the AlN layer before the second heat treatment, Si ions were implanted to a depth of 0.1 μm from the surface of the AlN layer, but in the AlN layer after the second heat treatment, the implanted Si had diffused to a depth of about 1 μm, similar to Example 1. In the AlN layer after the second heat treatment, the average Si concentration in the vicinity of the surface of the AlN layer was 3×10 18 cm -3 In the AlN layer after the second heat treatment, the oxygen concentration was lower than that before the second heat treatment, similarly to Example 1. In the AlN layer after the second heat treatment, the average oxygen concentration in the area from the surface of the AlN layer to a depth of 0.2 μm to 0.5 μm was 5×1017 cm -3 It was.
[0078] In addition, in FIG. 5, the graphs of the Si concentration and the oxygen concentration in the depth direction of the AlN layer after the Si ion implantation in Example 2 are each shown by a dashed line, and the graphs of the Si concentration and the oxygen concentration in the depth direction of the AlN layer after the second heat treatment in Example 2 are each shown by a solid line. The graph on the right side of FIG. 5 shows the Si concentration. The graph on the left side of FIG. 5 shows the oxygen concentration. In FIG. 5, the vertical axis of each graph is the concentration (cm -3 ), and the horizontal axis is depth (μm). In addition, in Fig. 6, the carbon concentration and hydrogen concentration in the depth direction of the AlN layer after Si ion implantation in Example 2 are shown by dashed lines, and the carbon concentration and hydrogen concentration in the depth direction of the AlN layer after the second heat treatment in Example 2 are shown by solid lines. The graph on the right side of Fig. 6 shows the Si concentration. The graph on the left side of Fig. 6 shows the oxygen concentration.
[0079] A TLM measurement was performed on the substrate with the conductive AlN epitaxial film, and it was found that a current flowed and the sheet resistance was 23 GΩ / □.
[0080] Comparative Example 1 A substrate with a conductive AlN epitaxial film of Comparative Example 1 was produced in the same manner as in Example 2, except that in the formation conditions for the second AlN layer, the stage temperature was set to 1360° C., which was 30° C. higher, to form the AlN layer.
[0081] The RMS of the surface of the AlN layer after the second AlN layer was formed was 0.52 nm.
[0082] The RMS of the surface of the AlN layer after the Si ion implantation was 0.5 nm. The average Si concentration in the range from the surface of the AlN layer to a depth of 0.1 μm was 3×10 19 cm -3 The average Si concentration near the surface of this AlN layer was 3 × 10 18 cm -3 The oxygen concentration in this AlN layer was 10 19 cm -3The average oxygen concentration near the surface of this AlN layer is about 3×10 19 cm -3 The oxygen concentration during epitaxial growth increases due to the high growth temperature in the second AlN layer formation process by MOCVD. In FIG. 7, the Si concentration and oxygen concentration in the depth direction of the AlN layer after Si ion implantation are shown by dashed lines. The graph on the right side of FIG. 7 shows the Si concentration. The graph on the left side of FIG. 7 shows the oxygen concentration. In FIG. 7, the vertical axis of each graph is the concentration (cm -3 ), and the horizontal axis is depth (μm). In addition, in FIG. 8, the carbon concentration and hydrogen concentration in the depth direction of the AlN layer after Si ion implantation are shown by dashed lines. The graph on the right side of FIG. 8 shows the carbon concentration. The graph on the left side of FIG. 8 shows the hydrogen concentration. In FIG. 8, the vertical axis of each graph is concentration (cm -3 ), and the horizontal axis is depth (μm).
[0083] The RMS of the surface of the AlN layer after the second heat treatment was 0.5 nm. In the AlN layer before the second heat treatment, Si ions were implanted to a depth of 0.1 μm from the surface of the AlN layer, but in the AlN layer after the second heat treatment, the implanted Si had diffused to a depth of about 1 μm, similar to Examples 1 and 2. In the AlN layer after the second heat treatment, the average Si concentration in the vicinity of the surface of the AlN layer was 2×10 18 cm -3 In the AlN layer after the second heat treatment, the oxygen concentration was lower than that before the second heat treatment, as in Example 1. However, in the AlN layer after the second heat treatment, the average oxygen concentration in the vicinity of the surface of the AlN layer was 7×10 17 cm -3 , which was higher than those in Examples 1 and 2.
[0084] When TLM measurements were performed on the substrate with the conductive AlN epitaxial film, no current flowed and the sheet resistance could not be measured properly.
[0085] Comparative Example 2 A substrate with a conductive AlN epitaxial film of Comparative Example 2 was produced in the same manner as in Example 2, except that the thickness of the second AlN layer was 0.5 μm and the total thickness of the AlN layer was 1 μm under the formation conditions of the second AlN layer. The RMS of the surface of the AlN layer after the formation of the second AlN layer was 0.5 nm.
[0086] The RMS of the surface of the AlN layer after the Si ion implantation was 0.5 nm. The average Si concentration in the range from the surface of the AlN layer to a depth of 0.1 μm was 3×10 19 cm -3 The average Si concentration near the surface of this AlN layer was 1×10 18 cm -3 The average oxygen concentration near the surface of this AlN layer was 8 × 10 17 cm -3 The diffusion of oxygen from the sapphire substrate during epitaxial growth was about 0.5 μm (up to the thickness of the first AlN layer), and the oxygen concentration on the surface side of this AlN layer was close to the value in Example 2 before the second heat treatment. In Fig. 9, the Si concentration and oxygen concentration in the depth direction of the AlN layer after Si ion implantation are shown by dashed lines. In Fig. 10, the carbon concentration and hydrogen concentration in the depth direction of the AlN layer after Si ion implantation are shown by dashed lines.
[0087] The RMS of the surface of the AlN layer after the second heat treatment at 1600°C was 0.4 nm. In the AlN layer before the second heat treatment, Si ions were implanted to a depth of 0.1 μm from the surface of the AlN layer, but in the AlN layer after the second heat treatment, the implanted Si had diffused to a depth of approximately 0.4 μm. In the AlN layer after the second heat treatment, the average Si concentration near the surface of the AlN layer was 1×10 19 cm -3 In the AlN layer after the second heat treatment, the oxygen concentration was higher than that before the second heat treatment. In the AlN layer after the second heat treatment, the average oxygen concentration in the area from the surface of the AlN layer to a depth of 0.2 μm to 0.5 μm was 2×10 19 cm -39, the Si concentration and oxygen concentration in the depth direction of the AlN layer after the second heat treatment in Comparative Example 2 are shown by solid lines. The graph on the right side of FIG. 9 shows the Si concentration. The graph on the left side of FIG. 9 shows the oxygen concentration. In FIG. 9, the vertical axis of each graph shows the concentration (cm -3 ), and the horizontal axis represents depth (μm). Also in FIG. 10, graphs of carbon concentration and hydrogen concentration in the depth direction of the AlN layer after the second heat treatment in Comparative Example 2 are shown by solid lines. The graph on the right side of FIG. 10 shows carbon concentration. The graph on the left side of FIG. 10 shows hydrogen concentration. In FIG. 10, the vertical axis of each graph is concentration (cm -3 ), and the horizontal axis is depth (μm).
[0088] When TLM measurements were performed on the substrate with the conductive AlN epitaxial film, no current flowed and the sheet resistance could not be measured properly.
[0089] Comparative Example 3 A substrate with a conductive AlN epitaxial film of Comparative Example 3 was produced in the same manner as Comparative Example 2, except that the temperature of the second heat treatment was set to 1230°C.
[0090] The RMS of the surface of the AlN layer after the formation of the second AlN layer was 0.5 nm. In the AlN layer before the second heat treatment, Si ions were implanted from the surface of the AlN layer to a depth of 0.1 μm, but in the AlN layer after the second heat treatment, the implanted Si was slightly diffused in the depth direction. In the AlN layer after the second heat treatment, the average Si concentration near the surface of the AlN layer was 3×10 18 cm -3 In the AlN layer after the second heat treatment, the oxygen concentration was slightly increased compared to before the second heat treatment. In the AlN layer after the second heat treatment, the average oxygen concentration near the surface of the AlN layer was 1×10 18 cm -3, which was higher than those in Examples 1 and 2. In Fig. 9, the graphs of the Si concentration and the oxygen concentration in the depth direction of the AlN layer after the second heat treatment in Comparative Example 3 are each shown by two-dot chain lines. In Fig. 10, the graphs of the carbon concentration and the hydrogen concentration in the depth direction of the AlN layer after the second heat treatment in Comparative Example 3 are each shown by two-dot chain lines.
[0091] When TLM measurements were performed on the substrate with the conductive AlN epitaxial film, no current flowed and the sheet resistance could not be measured properly.
[0092] Comparative Example 4 In Comparative Example 3, the total dose during ion implantation was 1×10 16 cm -2 A substrate with a conductive AlN epitaxial film was produced in the same manner as in Comparative Example 3, except that the amount of AlN was increased to 1000.
[0093] The RMS of the surface of the AlN layer after the Si ion implantation was 0.6 nm.
[0094] The RMS of the surface of the AlN layer after the second heat treatment was 13 nm. In the AlN layer after the second heat treatment, the average Si concentration near the surface of the AlN layer was 2×10 19 cm -3 In the AlN layer after the second heat treatment, the average oxygen concentration near the surface of the AlN layer was 1×10 18 cm -3 , which was higher than those in Examples 1 and 2. In FIG. 11, the solid lines show the Si concentration and oxygen concentration in the depth direction of the AlN layer after the second heat treatment in Comparative Example 4. The graph on the right side of FIG. 11 shows the Si concentration. The graph on the left side of FIG. 11 shows the oxygen concentration. In FIG. 11, the vertical axis of each graph shows the concentration (cm -3 ), and the horizontal axis is depth (μm). Also, in Fig. 12, a graph of the Si concentration and oxygen concentration in the depth direction of the AlN layer after the second heat treatment in Comparative Example 4 is shown by a solid line. The graph on the right side of Fig. 11 shows the Si concentration. The graph on the left side of Fig. 11 shows the oxygen concentration. In Fig. 11, the vertical axis of each graph is concentration (cm-3 ), and the horizontal axis is depth (μm).
[0095] When TLM measurements were performed on the substrate with the conductive AlN epitaxial film, no current flowed and the sheet resistance could not be measured properly.
[0096] The results of Examples 1 and 2 and Comparative Examples 1 to 4 explained above are shown in Table 1.
[0097] [Table 1]
[0098] As is clear from Table 1, in the substrates with conductive AlN epitaxial film according to Examples 1 and 2, the AlN layer after the implantation of Si ions and the heat treatment has high surface flatness and is conductive. In contrast, in the substrates with conductive AlN epitaxial film according to Comparative Examples 1 to 3, the AlN layer after the implantation of Si ions and the heat treatment has high surface flatness but is not conductive. In the substrate with conductive AlN epitaxial film according to Comparative Example 4, the AlN layer after the implantation of Si ions and the heat treatment has low surface flatness and is not conductive. A comparison between the Example and Comparative Example 1 reveals that the average oxygen concentration in the vicinity of the surface of the AlN layer in the AlN layer formation step was 2×10 18 cm -3 If the oxygen concentration is higher than 6×10, the average oxygen concentration near the surface will be 6×10 even if oxygen is desorbed from the surface by the second heat treatment. 17 cm -3 It was found that the conductivity could not be obtained because the Si near the surface could not be activated and the conductivity could not be obtained. From a comparison of the embodiment with comparative examples 2 and 3, it was found that when the thickness of the AlN layer was thin, the oxygen near the surface increased due to the oxygen diffused from the sapphire substrate during the second heat treatment, and the conductivity could not be obtained.
[0099] In this manner, it is possible to provide a substrate with a conductive AlN epitaxial film, which has a high surface flatness and an n-type AlN layer having a predetermined electrical conductivity on a sapphire substrate, and a method for manufacturing the same.
[0100] In addition, the configurations disclosed in the above embodiments (including other embodiments, the same applies below) can be applied in combination with configurations disclosed in other embodiments, provided no contradiction arises. Furthermore, the embodiments disclosed in this specification are illustrative, and the embodiments of the present invention are not limited thereto, and can be appropriately modified within the scope that does not deviate from the purpose of the present invention. [Industrial Applicability]
[0101] The present invention can be applied to a substrate with a conductive AlN epitaxial film having an n-type AlN layer on a sapphire substrate, and to a method for manufacturing the same. [Explanation of symbols]
[0102] 1 Sapphire substrate 2 AlN layer 21 First AlN layer 22 Second AlN layer 100 Conductive AlN epitaxial film substrate
Claims
1. A sapphire substrate; an AlN layer formed on the sapphire substrate; The AlN layer is The thickness is 2 μm or more and 10 μm or less, The average Si concentration in the range of 0.2 μm to 0.5 μm deep from the surface on the side opposite to the sapphire substrate is 1×10 18 cm -3 Above 1 x 10 19 cm -3 is as follows: The average oxygen concentration in the range of 0.2 μm to 0.5 μm deep from the surface is 6×10 17 cm -3 A substrate with a conductive AlN epitaxial film, which is as follows:
2. 2. The substrate with a conductive AlN epitaxial film according to claim 1, wherein the root mean square height of the surface is 1 nm or less.
3. an AlN layer formation step of forming an AlN layer on a sapphire substrate at a growth temperature of 1400° C. or less to a thickness of 2 μm or more; an ion implantation step of implanting Si ions into a surface of the AlN layer opposite to a surface facing the sapphire substrate; a heat treatment step of heat treating the AlN layer and the sapphire substrate at a temperature of 1300° C. or higher in a nitrogen atmosphere; The dose of the Si ions in the ion implantation step is 2×10 15 cm -2 is less than the ion implantation step is performed such that an average Si concentration in a range from the surface to a depth of 0.2 μm to 0.5 μm is 1×10 18 cm −3 or more and 1×10 19 cm −3 or less; The heat treatment step is a step of increasing the average oxygen concentration in the range of 0.2 μm to 0.5 μm deep from the surface to 6×10 17 cm -3 A method for producing a substrate with a conductive AlN epitaxial film comprising:
4. The AlN layer forming step includes: a first AlN layer forming step of forming a first AlN layer as the AlN layer on the sapphire substrate at a growth temperature of 1400° C. or less; a preliminary heat treatment step of heat treating the first AlN layer and the sapphire substrate at a temperature higher than a growth temperature of the first AlN layer; 4. The method for producing a substrate with a conductive AlN epitaxial film according to claim 3, further comprising: a second AlN layer forming step of forming a second AlN layer as said AlN layer on said first AlN layer at a growth temperature of 1400° C. or less.
5. In the AlN layer forming step, the average oxygen concentration in the range of 0.2 μm to 0.5 μm deep from the surface is set to 2×10 18 cm -3 5. The method for producing a substrate with a conductive AlN epitaxial film according to claim 3, wherein:
Citation Information
Patent Citations
Process for producing aluminium based iii nitride crystal and crystal multilayer substrate
JP2007042854A
Method of manufacturing n-type aluminum-nitride and semiconductor device
JP2007173744A
Aluminum nitride single crystal substrate, laminate, and method for producing the same
JP2010089971A
Group iii nitride semiconductor light-emitting element
JP2019004178A